Risk and Management of Gallstone Disease in Patients Submitted to Bariatric Surgery: A Systematic Review and A Bayesian meta-analysis - Filipe André Amorim Cruz (2022)
Background: Frequency and management of gallstone disease (GD) in bariatric patients, including the role of routine prophylactic concomitant cholecystectomy (CCY), is still a matter of debate. This study aims to assess the risk of de novo GD in patients undergoing bariatric surgery (BS) and their predictive factors, as well as mortality and morbidity in prophylactic CCY compared to BS alone. Methods: We performed a systematic review, searching PubMed, EMBASE, and Web of Science until April 2021. This study analysed the number of patients with asymptomatic or symptomatic GD; and the postoperative complications in patients who underwent CCY during BS. We performed a Bayesian meta-analysis to estimate the risk of GD development after BS and the morbidity and mortality associated with BS alone versus BS + prophylactic CCY. Sources of heterogeneity were explored by meta-regression analysis. Results: The risk of de novo post bariatric GD was 20.7% (95% credible interval [95%CrI]=13.0-29.7%; I2=75.4%), and of symptomatic GD was 8.2% (95%CrI=5.9-11.1%; I2=66.9%). Pre-operative average BMI (OR=1.04; 95%CrI=0.92-1.17) and female patients' proportion (OR=1.00; 95%CrI=0.98-1.04) were not associated with increased risk of symptomatic GD. BS + prophylactic CCY was associated with 97% probability of higher number of postoperative major complications compared to BS alone (OR=1.74, 95%CrI=0.97-3.55; I2=56.5%). Mortality was not substantially different between the two approaches (OR=0.79; 95%CrI=0.03-3.02; I2=20.7%). Conclusion: The risk of de novo symptomatic GD after BS is low. Although mortality is similar between groups, odds of major postoperative complications were higher in patients submitted to BS + prophylactic CCY. It is still arguable if prophylactic CCY is a proper approach for patients with preoperative lithiasic gallbladder.